Soluções de viscosidade para o infinito-laplaciano - Lucas Martins Rocha (2018)
In this work, our main goal is to present the results obtained by Marian Bocea e Mihai Mihailescu in the article [2], where they seek to treat the exitence of nonnegative solutions for a class of problems depending on a real parameter and involving the -Laplacian operator. Some results used through the article were presented in [15], by Petri Juutinen, Peter Lindqvist and Juan J. Manfredi, in special those which involve the first eigenvalue of the -Laplacian.